The Effects of Desflurane and Propofol on the Release of Thyroid Hormones in Euthyroid Patients Undergoing Elective Lumbar Discectomy - (:unkn) unknown (AVES, 2015)
Objective: In this study, we aimed to compare the effects of desflurane and propofol on the release of thyroid hormones in euthyroid patients undergoing single-level lumbar discectomy. Methods: The study group included 21-65-year-old American Society of Anesthesiology (ASA) I-II euthyroid 40 patients undergoing elective single-level lumbar discectomy. They were randomly divided into 2 groups (n=20). In the maintenance of anaesthesia, Group D received desflurane inhalational anaesthesia and remifentanil infusion, and Group P received propofol and remifentanil IV infusions. Four blood samples for the determination of plasma levels of free triiodothyronine (FT3), free thyroxine (FT4) and thyrotropin (TSH) were collected 5 min before and 60 min after the induction of anaesthesia and 60 min and 24 h after the surgery. Results: Plasma TSH levels in both groups reached the highest levels at the first postoperative hour and returned to the preoperative levels 24 hours after the surgery. Regarding plasma FT3 levels, there were no significant differences within and between groups. There were no significant differences in plasma FT4 levels within the patients of Group P, but in Group D, FT4 levels reached its peak in the first hour of anaesthesia induction and returned back to preoperative levels 24 hours postoperatively (p<0.05). Conclusion: Further studies are needed to confirm our findings and evaluate patients with thyroid gland pathologies.
Keywords: Thyroid gland; desflurane; propofol; ANESTHESIA; SURGERY; STRESS